Intelligence, Errors and Strategic Choices in the Repeated Prisoners' Dilemma - Eugenio Proto; Aldo Rustichini; Andis Sofianos (Center for Economic Studies and ifo Institute (CESifo), 2020)
A large literature in behavioral economics has emphasized in the last decades the role of individual differences in social preferences (such as trust and altruism) and in influencing behavior in strategic environments. Here we emphasize the role of attention and working memory, and show that social interactions among heterogeneous groups are likely to be mediated by differences in cognitive skills. Our design uses a Repeated Prisoner's Dilemma, and we compare rates of cooperation in groups of subjects grouped according to their IQ, with those in combined groups. While in combined groups we observe higher cooperation rates and profits than in separated groups (with consistent gains among lower IQ subjects and relatively smaller losses for higher IQ subjects), higher IQ subjects become less lenient when they are matched with lower IQ subjects than when they play separately. We argue that this is an instance of a general phenomenon, which we demonstrate in an evolutionary game theory model, where higher IQ among subjects determines - through better working memory - a lower frequency of errors in strategy implementation. In our data, we show that players indeed choose less lenient strategies in environments where subjects have higher error rates. The estimations of errors and strategies from the experimental data are consistent with the hypothesis and the predictions of the model.
Keywords: C73; C91; C92; B83; 330; repeated prisoner's dilemma; cooperation; intelligence; IQ; strategy; error in transition